SYTEMATIC LITERATURE REVIEW (SLR) AND BIBLIOMETRIC ANALYSIS ON JOB CRAFTING - Rochmadona, Arlda; Malay, M. Nursalim; Hidayati, Ira (Universitas Mercu Buana Jakarta, 2024)
The 5.0 revolution era has transformed work into work with flexibility. Flexibility at work allows employees to work anywhere, but this flexibility can cause psychological fatigue where employees cannot differentiate between work and rest time. Therefore, employees redesign tasks and jobs according to their preferences, which is called job crafting. This research aims to explain what factors can cause employees in the 5.0 era to carry out job crafting. The research was conducted with a systematic literature review (SLR), using the PRISMA (Preferred Reporting Items for Systematic Review and Meta-Analysis) and Bibliometric methods to filter topics, sub-topics and journals that fit the criteria. Thus, 41 journals were obtained from databases, namely ScienceDirect, Emerald, PubMed, and SemanticScholar. Based on the results of research that has been conducted, job crafting is influenced by autonomy (25%), work environment (18%), job demands (16%), job resources (15%), job satisfaction (13%), characteristics (13%). Employees who do job crafting are usually very motivated to develop, so employees will look for ways to increase their work contribution.